Vestibular Thresholds: A Review of Advances and Challenges in Clinical Applications - Kobel, Megan J.; Wagner, Andrew R.; Merfeld, Daniel M.; Mattingly, Jameson K. (Frontiers in Neurology, 2021)
Vestibular disorders pose a substantial burden on the healthcare system due to a high prevalence and the severity of symptoms. Currently, a large portion of patients experiencing vestibular symptoms receive an ambiguous diagnosis or one that is based solely on history, unconfirmed by any objective measures. As patients primarily experience perceptual symptoms (e.g., dizziness), recent studies have investigated the use of vestibular perceptual thresholds, a quantitative measure of vestibular perception, in clinical populations. This review provides an overview of vestibular perceptual thresholds and the current literature assessing use in clinical populations as a potential diagnostic tool. Patients with peripheral and central vestibular pathologies, including bilateral vestibulopathy and vestibular migraine, show characteristic changes in vestibular thresholds. Vestibular perceptual thresholds have also been found to detect subtle, sub-clinical declines in vestibular function in asymptomatic older adults, suggesting a potential use of vestibular thresholds to augment or complement existing diagnostic methods in multiple populations. Vestibular thresholds are a reliable, sensitive, and specific assay of vestibular precision, however, continued research is needed to better understand the possible applications and limitations, especially with regard to the diagnosis of vestibular disorders.